Novel neuroprotective action of prothymosin alpha‐derived peptide against retinal and brain ischemic damages. (28th January 2013) - Halder, Sebok Kumar; Matsunaga, Hayato; Yamaguchi, Haruka; Ueda, Hiroshi
Abstract Prothymosin alpha (ProTα), a nuclear protein, is implicated in the inhibition of ischemia‐induced necrosis as well as apoptosis in the brain and retina. Although ProTα has multiple biological functions through distinct regions in its sequence, it has remained which region is involved in this neuroprotection. This study reported that the active core peptide sequence P30 (amino acids 49–78) of ProTα exerts its full survival effect in cultured cortical neurons against ischemic stress. Our in vivo study revealed that intravitreous administration of P30 at 24 h after retinal ischemia significantly blocks the ischemia‐induced functional damages of retina at day 7. In addition, P30 completely rescued the retinal ischemia‐induced ganglion cell damages at day 7 after the ischemic stress, along with partial blockade of the loss of bipolar, amacrine, and photoreceptor cells. On the other hand, intracerebroventricular (3 nmol) or systemic (1 mg/kg; i.v.) injection of P30 at 1 h after cerebral ischemia (1 h tMCAO) significantly blocked the ischemia‐induced brain damages and disruption of blood vessels. Systemic P30 delivery (1 mg/kg; i.v.) also significantly ameliorated the ischemic brain caused by photochemically induced thrombosis. Taken together, this study confers a precise demonstration about the novel protective activity of ProTα‐derived small peptide P30 against the ischemic damages in vitro and in vivo.